2013
DOI: 10.1002/tect.20082
|View full text |Cite
|
Sign up to set email alerts
|

Uplift and denudation history of the eastern Dead Sea rift flank, SW Jordan: Evidence from apatite fission track thermochronometry

Abstract: The Dead Sea rift (DSR), developed along the Dead Sea transform plate boundary, is characterized by salient flanks and morphotectonic asymmetry. Apatite fission track thermochronology (AFT) along ~1200 m high vertical profiles in Neoproterozoic basement and overlying Cambrian sandstone in southwestern Jordan is used to reconstruct timing, magnitude, and rate of uplift and denudation of the eastern DSR flank and examine its relationship to rift development and its flank landscape. Time‐temperature models based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 112 publications
(157 reference statements)
6
20
0
Order By: Relevance
“…Our study demonstrates that the separation between Africa and Arabia had two phases: its initiation began in the Eocene-Oligo cene, and intensifi ed since the late Oligocene-early Miocene. This two-phase scenario is in agreement with fi ssion-track analyses (e.g., Omar and Steckler, 1995;Feinstein et al, 2000Feinstein et al, , 2004Feinstein et al, , 2010.…”
Section: Regional Evolution-two-stage Scenario For Continental Breakupsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study demonstrates that the separation between Africa and Arabia had two phases: its initiation began in the Eocene-Oligo cene, and intensifi ed since the late Oligocene-early Miocene. This two-phase scenario is in agreement with fi ssion-track analyses (e.g., Omar and Steckler, 1995;Feinstein et al, 2000Feinstein et al, , 2004Feinstein et al, , 2010.…”
Section: Regional Evolution-two-stage Scenario For Continental Breakupsupporting
confidence: 82%
“…This two-stage morphotectonic evolution model for the Afar-southern Levant region is clearly demonstrated by fi ssion-track analysis presented by Omar and Steckler (1995) from the Red Sea region and by Feinstein et al (2000Feinstein et al ( , 2004Feinstein et al ( , 2010 from the northern tip of the Gulf of Aqaba. Both studies indicated that, besides the well-known rifting and rock uplift phase centered in the early Miocene, an initial early Oligocene stage was clearly identifi ed.…”
Section: Regional Evolution-two-stage Scenario For Continental Breakupmentioning
confidence: 71%
“…The temporal variation of uplift within this 30 Ma period can be constrained in different ways. First, thermochronometric measurements are used to determine rates of denudation at spot locations [Kohn and Eyal, 1981;Bohannon et al, 1989;Menzies et al, 1997;Feinstein et al, 2013]. At present, these spot measurements are sparse and dominated by localities in Yemen.…”
Section: Introductionmentioning
confidence: 99%
“…Our thermomechanical modeling demonstrates that narrow asymmetric half‐graben, bounded by a planar active normal eastern fault and a slightly curved less active western fault (Figures c and b), observed also in the field [ ten Brink et al ., ; Wdowinski and Zilberman , ; Feinstein et al ., ], originated in the early stages of the rift evolution. During the entire rifting period (circa 5 Ma), deformations concentrated at these normal faults.…”
Section: Resultsmentioning
confidence: 99%
“…The topography at the southern segment of the DSF shows a distinct asymmetry [ Ben‐Avraham and Zoback , ; Wdowinski and Zilberman , , ]. The larger subsidence and higher uplift are observed at the eastern border fault [ ten Brink et al ., ; Feinstein et al ., ]. East from the rift axis, the elevation rises sharply to 1400–1700 m above sea level (asl) at the peaks of Transjordan Mountain Belt (TJMB), located 20–30 km away (Figure a).…”
Section: Geodynamics Of the Dead Sea Faultmentioning
confidence: 99%